Supramolecular Hybrid Hydrogel Synthesis and Characterization for Burn Wound Dressing Applications - Stafford, Zosia. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Ayse Asatekin.; Committee: Ayse Asatekin, Matthew Panzer, and Aslıhan Gökaltun.; Keywords: Polymer chemistry, Chemical engineering, and Materials Science.